Analysis of Radiation Dose Received by Radiation Workers With Physical and Biological Dosimeters in The Radiology Unit of Sanjiwani Hospital - Mas Janudinata, Gde Ari; Sutapa, Gusti Ngurah; Kasmawan, I Gde Antha; Made Suryatika, Ida Bagus; Artawan, I Nengah; Trisnawati, Ni Luh Putu (Kappa Journal, 2025)
This study aims to evaluate the impact of radiation exposure on the health of radiation workers at RSUD Sanjiwani Gianyar over the past five years. The evaluation was conducted through a physical approach, measuring radiation doses using Thermoluminescent Dosimeter (TLD), and a biological approach by analyzing the total leukocyte count and its components, namely neutrophils, lymphocytes, monocytes, and eosinophils. The results showed that the highest radiation dose was received by radiology specialists at 0.921 mSv, followed by medical physicists at 0.905 mSv, and radiographers at 0.894 mSv. This variation reflects differences in radiation exposure levels based on each profession's tasks and positions. Leukocyte and component analysis indicated that all values were within normal ranges. Although statistical tests showed significant differences in neutrophil levels between professions, overall radiation doses and leukocyte levels were within the safe limits set by PERKA BAPETEN No. 4 of 2013. The findings underline that radiation protection measures at RSUD Sanjiwani have been effective in minimizing health risks from radiation exposure. However, regular dose monitoring and health evaluations are necessary to ensure long-term protection for radiation workers.